2017
DOI: 10.1038/srep41045
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for positive selection and recombination hotspots in Deformed wing virus (DWV)

Abstract: Deformed wing virus (DWV) is considered one of the most damaging pests in honey bees since the spread of its vector, Varroa destructor. In this study, we sequenced the whole genomes of two virus isolates and studied the evolutionary forces that act on DWV genomes. The isolate from a Varroa-tolerant bee colony was characterized by three recombination breakpoints between DWV and the closely related Varroa destructor virus-1 (VDV-1), whereas the variant from the colony using conventional Varroa management was sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
96
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(104 citation statements)
references
References 61 publications
5
96
2
1
Order By: Relevance
“…However, our results provide little support for this pattern via Pacbio or Sanger sequencing. We found no evidence of previously reported recombination within the N‐terminal region of the helicase gene (Dalmon et al ). Instead, we found limited evidence of recombination within the rdrp and lp genes, similar to reports from the UK (Moore et al ; Wang et al ).…”
Section: Discussioncontrasting
confidence: 91%
“…However, our results provide little support for this pattern via Pacbio or Sanger sequencing. We found no evidence of previously reported recombination within the N‐terminal region of the helicase gene (Dalmon et al ). Instead, we found limited evidence of recombination within the rdrp and lp genes, similar to reports from the UK (Moore et al ; Wang et al ).…”
Section: Discussioncontrasting
confidence: 91%
“…An increasing number of studies report the presence of recombinants between DWV-A /-B in nature 4649 , and it has been suggested that recombinants may be more virulent than DWV-A or -B, at least in honeybee pupae 48 . In the present study, we did not detect any mixed infections in our field samples to indicate the presence of recombinants.…”
Section: Discussionmentioning
confidence: 99%
“…This cloned DWV variant 24 was isolated from a heavily Varroa-infested colony typical for the USA and likely to be Varroa-selected, as evidenced by its transmission in Experiment 2. It cannot be ruled out that other DWV-like variants, namely the highly pathogenic DWV type B 6 , which has shown increased virulence 34,35 , or VDV1-DWV recombinants 810 could have replicative ability in Varroa mites, especially considering their preferable transmission by the mites 8,36 and the detection of VDV-1 negative strand RNA in the Varroa synganglions 23 . Investigation of the abilities of different DWV strains to replicate in the mites should be carried out using experimental procedures similar to those used in this study.…”
Section: Discussionmentioning
confidence: 99%